Link N Directly Targets IL-1β to Suppress Inflammation and Regulate Sensory Pain in Intervertebral Disc Degeneration - Michael P. Grant; Muskan Alad; Fajer Yousef; Laura M. Epure; John Antoniou; Fackson Mwale (Biomolecules)
Intervertebral disc (IVD) disease is typically characterized by the degradation of IVD tissue, secretion of inflammatory and painful factors, and hyperinnervation of the disc. The pro-inflammatory cytokine interleukin-1β (IL-1β) has been regarded as a principal factor in orchestrating disc degeneration. Link N (LN) is a peptide derived from the link protein that has been shown to promote extracellular disc regeneration even in an inflammatory milieu; however, no mechanism(s) has been described for their behaviour to date. Building on prior studies on LN, we hypothesize that LN directly inhibits IL-1β. IVD degeneration was experimentally induced in New Zealand white rabbits, followed by the injection of either sLN or saline as the vehicle control. To determine the expression of markers of pain, histology was performed. Cultured human Nucleus Pulposus disc cells (hNP) were used to determine the effects of LN on IL-1β-induced changes in gene expression, including the effects on IL-1β, TNFα, and IL6 signalling. Isolated murine dorsal root ganglia (DRG) neurons were used to assess the effect of LN on IL-1β-induced neuronal hyperactivity. LN significantly reduced IL-1β-induced NF-κB activation in a dose-dependent manner in disc cells and was further able to modulate IL-1β-induced gene expression, inflammatory mediators, and neurotrophic factors. Peptide docking simulations revealed that LN could interact with IL-1β. A direct interaction of LN and IL-1β was revealed through co-immunoprecipitation experiments. Although IL-1β was able to hypersensitize DRG neurons following a seven-day exposure, as demonstrated by Ca2+ imaging, this effect was significantly blunted when co-treated with LN. LN demonstrates a novel mechanism of action by directly inhibiting IL-1β, in addition to mitigating IL-1β-induced hypersensitivity in DRG neurons. These data suggest a potential role for LN in reducing discogenic pain.